2021
DOI: 10.22271/chemi.2021.v9.i2a.11871
|View full text |Cite
|
Sign up to set email alerts
|

Periodical changes in quality parameters of honey during storage and processing

Abstract: The effect of storage upto 15 months on apiary honey with an increase in storage period upto 15 months resulted in an increase in the refractive index, Pfund value, TRS, glucose, HMF and yeast and decrease in the moisture, pH and sucrose levels. The properties of honey changed with the advancement of storage. The honey when subjected to indirect heating at different temperatures revealed that moisture content of honey was reduced when heated beyond 50 0 C. A slight variation in TRS content was also observed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The amount of honey beekeepers can harvest highly depends on the level of management and appropriate volume of the hive provided to the bee colonies (Awraris et al, 2015). The mellisopalynological studies of Bengaluru honey samples revealed the richness of honey with pollen grains of Eucalyptus sp., followed by Pongamia pinnata, Azadirachta indica, Synedrilla nodiflora and Suregada angustifolia (Vijayakumar et al, 2020).…”
Section: Performance Of Beehives With Different Frames For Growth And...mentioning
confidence: 98%
“…The amount of honey beekeepers can harvest highly depends on the level of management and appropriate volume of the hive provided to the bee colonies (Awraris et al, 2015). The mellisopalynological studies of Bengaluru honey samples revealed the richness of honey with pollen grains of Eucalyptus sp., followed by Pongamia pinnata, Azadirachta indica, Synedrilla nodiflora and Suregada angustifolia (Vijayakumar et al, 2020).…”
Section: Performance Of Beehives With Different Frames For Growth And...mentioning
confidence: 98%
“…It is then acidified with 5 ml of concentrated sulphuric acid and quickly titrated the excess of iodine against standard sodium thiosulphate solution. By using 50 ml of water a blank was prepared and was run in place of honey solution [15][16][17]. The glucose content is calculated by using the formula, % of Glucose(W)= (B-S) × 0.004502×100/A B = Volume of Sodium thiosulphate solution required for the blank.…”
Section: Colour Intensitymentioning
confidence: 99%